Integrasi Computational Thinking dan Teori APOS pada Pembelajaran Matematika: Sebuah Systematic Literature Review - Hidayatulloh, Muhammad Syarif; Suweken, Gede; Suarsana, I Made; Sudiarta, I Gusti Putu (Media Pendidikan Matematika, 2026)
This study aims to synthesize global research trends and theoretical developments regarding the integration of APOS (Action, Process, Object, Schema) Theory and Computational Thinking (CT) in mathematics education over the past decade. The method used is a Systematic Literature Review (SLR) of 18 reputable journal articles with a time span of 2016–2026. The results of the review indicate that the integration of CT and APOS is not merely a pedagogical choice, but an epistemological necessity that forms a complementary symbiosis. On the one hand, APOS provides a structured cognitive map that reveals the urgency of providing scaffolding at the Action and Process stages to prevent missing stages in students who are still stuck at the basic computational level. On the other hand, empirical findings support the implementation of the M-APOS model which is proven to significantly improve CT abilities with Cohen's d of 1.57 raises a critical reciprocal hypothesis: that the CT pillars are suspected to act as facilitators that activate the effectiveness of the transition between APOS stages. This study concludes that designing learning tools such as diagnostic instruments, modules, and digital worksheets that position CT as a cognitive entry point in the APOS traversal is an urgent priority. This adaptive instructional design is projected to transform students from mere mechanical calculators into autonomous, reflective problem solvers with systemic thinking capabilities.